Environmental Kuznets Curve and Growth Source in Iran - Asghari, Maryam (Panoeconomicus, 2012)
Recent empirical research has examined the relationship between certain indicators of environmental degradation and income, concluding that in some cases an inverted U-shaped relationship, which has been called an environmental Kuznets curve (EKC), exists between these variables. The source of growth explanation is important for two reasons. First, it demonstrates how the pollution consequences of growth depend on the source of growth. Therefore, the analogy drawn by some in the environmental community between the damaging effects of economic development and those of liberalized trade is, at best, incomplete. Second, the source of growth explanation demonstrates that a strong policy response to income gains is not necessary for pollution to fall with growth. The aim of this paper investigates the role of differences source of growth in environmental quality of Iran. The results show the two growth resources in Iran cause, in the early stages, CO2 emission decreases until turning point but beyond this level of income per capita, economic growth leads to environmental degradation. I find a U relationship between environmental degradation (CO2 emission) and economic growth in Iran.Key words: FDI, Trade, Source of growth, Environment.JEL: Q56.